Characterization of CdxTeyOz/CdS/ZnO Heterostructures Synthesized by the SILAR Method - Suchikova, Yana; Kovachov, Sergii; Bohdanov, Ihor; Popova, Elena; Moskina, Aleksandra; Popov, Anatoli (MDPI, 2023)
CdxTeyOz/CdS/ZnO heterostructures were obtained by the SILAR method using ionic electrolytes. A CdS film was formed as a buffer layer for better adhesion of the cadmium-tellurium oxides to the substrate surface. In turn, the ZnO substrate was previously prepared by electrochemical etching to form a rough textured surface. In addition, an annealing mode was used in an oxygen stream to complete the oxidation process of the heterostructure surface. The resulting nanocomposite was investigated using RAMAN, XRD, SEM, and EDX methods. We assume that the oxides CdO and TeO4 initially form on the surface and later evolve into TeO2 and TeO3 when saturated with oxygen. These oxides, in turn, are the components of the ternary oxides CdTeO3 and CdTe3O8. It should be noted that this mechanism has not been fully studied and requires further research. However, the results presented in this article make it possible to systematize the data and experimental observations regarding the formation of cadmium-tellurium films. © 2023 by the authors.--//-- This is an open access publication Suchikova Y., Kovachov S., Bohdanov I., Popova E., Moskina A., Popov A.; Characterization of CdxTeyOz/CdS/ZnO Heterostructures Synthesized by the SILAR Method (2023) Coatings, 13 (3), art. no. 639; DOI: 10.3390/coatings13030639; https://www.scopus.com/inward/record.uri?eid=2-s2.0-85152654514&doi=10.3390%2fcoatings13030639&partnerID=40&md5=3ea72367de513202fc87a3a5b99df07f published under the CC BY 4.0 licence.
The study was supported by the Ministry of Education and Science of Ukraine via Project No. 0122U000129 “The search for optimal conditions for nanostructure synthesis on the surface of A3B5, A2B6 semiconductors and silicon for photonics and solar energy” and Project No. 0121U10942 “Theoretical and methodological bases of system fundamentalization of the future nanomaterials experts training for productive professional activity”. In addition, the research of A.P. and Y.S. was partly supported by COST Action CA20129 “Multiscale Irradiation and Chemistry Driven Processes and Related Technologies” (MultIChem). A.P. thanks to the Institute of Solid-State Physics, University of Latvia. ISSP UL as the Center of Excellence is supported through the Framework Program for European universities, Union Horizon 2020, H2020-WIDESPREAD-01–2016–2017-TeamingPhase2, under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES; annealing; electrolytes; films; heterostructures; oxides; SILAR method